Prediction of Sanding Likelihood Intervals Using Different Approaches - Al Said Naji, Jassim M.; Abdul-Majeed, Ghassan H.; Alhuraishawy, Ali K.; Abbas, Abbas R. (Journal of Petroleum Research and Studies, 2023)
Sand production is undesirable matters, occurring in wells that are producing from sand reservoirs. It causes many problems such as erosion and grains accumulation in downhole and surface equipment’s, and formation subsidence. Important stage in sanding problem solution is a prediction of likelihood sand production intervals. In present paper, a vertical well X1 that is producing from Asmari reservoir in Y field at southern Iraq was selected for study. Asmari reservoir was classified to six units: A, B1, B2, B3, B4, and C. B zones consisted from sandstone with others rock types. Eight approaches were used for prediction sanding onset intervals by dealing with X1 well as open hole completion. Utilized eight prediction methods are compressional sonic wave (CSW), unconfined compressive strength (UCS), total porosity (PHIT), shear modulus to bulk compressibility (G/Cb), B-Index, Schlumberger index (S- Index), combined index (Ec-Index) and critical drawdown pressure (CDDP). All these methods performed based on 2462 measured points of CSW, sonic shear wave log (SSW), and density log (DL). Sand production likelihood intervals was selected by determination of cutoff values of adopted methods. Sand is possible to occur if interval has values lower than cutoff values of G/Cb, UCS, B-Index, S-Index, Ec, and CDDP and greater than cutoff values of CSW, and PHIT. Obtained cutoff values of eight approaches were 800 x 109 psi2, 36 Mpa, 0.2, 80 us/ft, 10000 Mpa, 108 Mpa, and 2700 Mpa, of G/Cb, UCS, PHIT, CSW, B-Index, S-Index, and Ec respectively. As well as sand production is possible to occur of bottomhole flowing pressure lower than calculated CDDP. Some Intervals had high CDDP that referred to abnormal pressure zones consisted from shale. Determination of sand onset intervals is a key for selecting best methods for controlling.